Formins: Emerging Players in the Dynamic Plant Cell Cortex - Fatima Cvrčková (Scientifica)
Formins (FH2 proteins) are an evolutionarily conserved family of eukaryotic proteins, sharing the common FH2 domain. While they have been, until recently, understood mainly as actin nucleators, formins are also engaged in various additional aspects of cytoskeletal organization and signaling, including, but not limited to, the crosstalk between the actin and microtubule networks. A surprising diversity of domain organizations has been discovered among the FH2 proteins, and specific domain setups have been found in plants. Seed plants have two clades of formins, one of them (Class I) containing mostly transmembrane proteins, while members of the other one (Class II) may be anchored to membranes via a putative membrane-binding domain related to the PTEN antioncogene. Thus, plant formins present good candidates for possible mediators of coordination of the cortical actin and microtubule cytoskeletons, as well as their attachment to the plasma membrane, that is, aspects of cell cortex organization likely to be important for cell and tissue morphogenesis. Although experimental studies of plant formin function are hampered by the large number of formin genes and their functional redundancy, recent experimental work has already resulted in some remarkable insights into the function of FH2 proteins in plants.